Suplementasi vitamin A dan asupan zat gizi dengan serum retinol dan morbiditas anak 1-3 tahun - Milliyantri Elvandari; Dodik Briawan; Ikeu Tanziha (Jurnal Gizi Klinik Indonesia, 2017)
Background: Morbidity of infectious diseases in developing countries is a public health concern because the prevalence is still high, particularly for children under five years. Vitamin A  intake was one of factors that may affect morbidity.Objective: The objective of this study was to analyze  relation between vitamin A supplementation, nutrition intake with vitamin A status and relation between vitamin A supllementation, nutrition intake, vitamin A status with morbidity.Method: The study was an cross-sectional study. This research was conductedin February-March 2016 in Kudus and Grobogan Central Java. Subjectsin this study were children aged 1-3 years(n=140). Retinol serum was collected by taking blood sample through the vein then was analyzed using HPLC, nutrients intake with food recall 2x24jam, and structured interviews with mother children. Data were analyzed with Chi-Square test.Results: The study found that 68 subjects (48.6%) were not took vitamin A supplemantation capsule. Prevalence of childrens had nutrient deficiency (<90% RDA) were relatively high 68.6% energy; 47.1% protein; 70.7% fat; and the prevalence of vitamin A defeciency (<77% RDA)  were relatively high 60%. A number of 24.2% subjects had low retinol serum (<20μg/dl). Supplementation vitamin A, fat and vitamin A intake correlated with retinol serum (p<0.05). Supplementation vitamin A, intake of vitamin A, vitamin C, zinc and retinol serum correlated with morbidity (p<0.05).Conclusion: Childrens who were not took vitamin A supplemantation capsule, deficiency intake of vitamin A, vitamin C, zinc and low retinol serum had higher morbidity.